Colombia, Panama and the Pan-American Highway: Agreements and Desagreements (2012)
This article is an analysis basedon the results ofa descriptive and explanatory research projectwhich take up againthe controversyarisen in the last decades about the construction ofthePan-American HighwayinThe Darien Gap,where this project has been stalled for more than 30years because of the conflict of interests between the groups involved. The aim is to show, from the theoretical perspectiveof thecomplex interdependence, thatthe construction ofthe Pan-American Highwayin the DarienGapprovides ajointroad infrastructurethat makes easier the continental integration,at the same time it benefitsthe relations between Colombiaand Panama and its influencein South America, according to thepremise that the cooperation between related territories ensuresthe necessary dimensionstodevelop a highdegree of economic andpolitical power